The Knossos tablets - Melena, José L.; Firth, Richard J. (INSTAP Academic Press, 2019)
"An updated transliteration of the Linear B tablets from the Bronze Age site of Knossos, Crete, Greece is presented together with lists of scribal hands, find spots, and other pertinent information and figures"--